Preparation of Low Cost Solid State Silver Sulfide Based Bromide Selective Electrodes - Yadav, Amar Prasad (Journal of Nepal Chemical Society, 2012)
Preparation and performance of a cost effective silver sulfide based bromide selective membrane is described. A solid contact between membrane and body of the electrode was examined as an ion-selective electrode by determining S2- and Br- ions by direct potentiometry. A linear response to bromide ion from 2 x 10-5 to 10-1 M with a slope of 57.3 mV per decade [Br-] is observed. The membrane has a very short response. It gives excellent results as an indicator electrode for potentiometric titration. DOI: http://dx.doi.org/10.3126/jncs.v27i1.6668 J. Nepal Chem. Soc., Vol. 27, 2011 100-106